The Challenge of Change - Dickerson, Mark O. (ARCTIC, 2000)
At their annual meeting on April 13, 2000, the Board of Directors of The Arctic Institute of North America bid farewell to Mike Robinson. . The search for a new Executive Director has been successful. Karla Jessen Williamson has accepted the Directorship. She will begin her tenure on September 15, 2000. . In a future issue of Arctic, Karla will tell us more about herself, her research, and her goals for the Arctic Institute of North America. . In an era of significant social, economic, and political changes North of 60, she is well positioned to lead AINA in meeting research challenges not only in Canada's North, but in all circumpolar regions of the world.